Activator of thyroid and retinoid receptor increases sorafenib resistance in hepatocellular carcinoma by facilitating the Warburg effect. Issue 6 (13th June 2020) - Ma, Luyuan; Liu, Wenpeng; Xu, An; Ji, Quanbo; Ma, Yongfu; Tai, Yanhong; Wang, Yadong; Shen, Chuan; Liu, Ying; Wang, Tao; Han, Juqiang; Zhao, Caiyan
Abstract: Sorafenib resistance is a major challenge in the therapy for advanced hepatocellular carcinoma (HCC). However, the underlying molecular mechanisms of HCC resistance to sorafenib remain unclear. Activator of thyroid and retinoid receptor (ACTR, also known as SRC‐3), overexpressed in HCC patients, plays an important oncogenic role in HCC; however, the link between ACTR and sorafenib resistance in HCC is unknown. Our study demonstrated that ACTR was one of the most upregulated genes in sorafenib‐resistant HCC xenografts. ACTR increases sorafenib resistance through regulation of the Warburg effect. ACTR promotes glycolysis through upregulation of glucose uptake, ATP and lactate production, and reduction of the extracellular acidification and the oxygen consumption rates. Glycolysis regulated by ACTR is vital for the susceptibility of HCC to sorafenib in vitro and in vivo. Mechanistically, ACTR knockout or knockdown decreases the expression of glycolytic enzymes. In HCC patients, ACTR expression is positively correlated with glycolytic gene expression and is associated with poorer outcome. Furthermore, ACTR interacts with the central regulator of the Warburg effect, c‐Myc, and promotes its recruitment to glycolytic gene promoters. Our findings provide new clues regarding the role of ACTR as a prospective sensitizing target for sorafenib therapy in HCC. Abstract : Sorafenib resistance is a major challenge in the therapy for advanced hepatocellular carcinoma (HCC). However, the underlying molecular mechanisms of HCC resistance to sorafenib remain unclear. Here, the authors find that ACTR increases the sorafenib resistance phenotype and suppresses sorafenib‐induced apoptosis through upregulation of the Warburg effect, providing new clues regarding ACTR as a prospective sensitizing target in sorafenib therapy.